The use of intuitive AF-based modelling for the understanding of activation and signalling through insulin-like receptors - Andrzej M. Brzozowski; Talha Shafi; Olga V. Moroz; Pierre De Meyts (Frontiers in Endocrinology)
The understanding of the conformational events occurring through the Insulin-like Receptors (ILRs) upon binding of their cognate hormones is very advanced, thanks to multidisciplinary efforts and breakthroughs, from molecular/cell biology to structural studies. However, the full length structures of this class of Tyrosine Kinase (TK) receptors are still not available. This is due to fundamental methodological constraints: a need for lipid micelles or nanodiscs required for the stabilisation of the full-length single receptor molecule. They tend to occlude the transmembrane (TM) and intra-cellular parts of the receptors, which, together with their inherent dynamic characters, prohibits - so far - determination of their full, continuous structures. Nevertheless, there is plenty of crystallographic evidences about separate TKs, some also with parts of the Juxtamembrane (JM) region that links the TM helices with the TKs. There are well over 40 known structures of the ectodomains (ECDs) of the ILRs in different complexes with hormones and their analogues, representing a wide spectrum of conformations. However, there is still a remaining question how a particular stage of ECD:hormone binding is translated into activation of the TKs. Here, we attempt to fill this ECD - TM-JM-TK structural gap by employing a simple AlphaFold2-based modelling of these regions, and combining AF2-derived models with the already determined ECD structures. This allows us to propose here a general ILRs activation model where the JM-TK close contacts with the inner leaf of the cell membrane contribute to the activation of the receptors. A possible dual role of the JM region in this process – both TK auto-inhibitory and stabilizing - has been highlighted as well. It also seems that the diverse natures of receptors:membrane lipid interactions require more experimental attention for the full understanding of the signal transduction through Insulin-like Receptors.